A preliminary investigation of occurrence of pharmaceuticals and personal care products in total suspended particulate matter in Ha Noi, Viet Nam - Hai Doan, Nguyen; Kadokami, Kiwao; Le Minh, Vu; Duong, Hanh Thi (Vietnam Journal of Science and Technology, 2024)
Air pollution has become a serious environmental issue in Viet Nam, particularly in large cities. There is little information regarding the presence of pharmaceuticals and personal care products (PPCPs) in suspended particulate matter in Ha Noi, Viet Nam. The present study screened 163 PPCPs from 12 total suspended particulate matter (TSP) samples collected in Ha Noi using a novel analytical method, the liquid chromatography-mass spectrometry-quadrupole time of flight-Sequential Window Acquisition of All Theoretical Fragment Ion Spectra method (LC-QTOF-MS-SWATH). We identified and quantified 6 of the 163 PPCPs. All of the 6 PPCPs were detected for the first time in TSP. The total concentration ranged from 37.3 to 401.0 pg m-3 (median: 143 pg m-3). The number of PPCPs detected per sample ranged from 1 to 5 (median: 3), and their figure found was higher in the nighttime than that of the daytime.